The role of fungi in fungal keratitis - Mills, Bethany; Radhakrishnan, Naveen; Karthikeyan Rajapandian, Siva Ganesa; Rameshkumar, Gunasekaran; Lalitha, Prajna; Prajna, N. Venkatesh (Experimental eye research, 2021)
Fungal keratitis (FK) accounts for approximately half of the microbial keratitis encountered in low middle income countries (LMICs) and predominantly affect the working rural-poor. FK causes significant morbidity with the majority of patients left with moderate or worse visual impairment and approximately 25% requiring expensive and often unsuccessful surgical interventions. The severity of FK and the resultant corneal damage or resolution can be attributed to i) the virulence and bioburden of the fungal pathogen, ii) the host defense mechanism and immune response and iii) sub-optimal diagnostics and anti-fungal treatment strategies. This review provides a comprehensive overview of the multifaceted components that drive FK progression and resolution, highlighting where knowledge gaps exist and areas that warrant further research. •Fungal keratitis is a serious public health problem with high rates of ocular morbidity.•The disease manifestation is a culmination of the interplay between the invading fungi and the host defence mechanism.•Different fungi have different virulence patterns.•Next generation sequencing and proteomics technologies will play a crucial role in the near future.•Targeted topical immunosuppressives with specific antifungals may be the key to achieve a good therapeutic outcome.